2010
DOI: 10.1007/s00705-010-0722-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of enterovirus 71 “double-recombinant” strains belonging to a novel genotype D originating from southern China: first evidence for combination of intratypic and intertypic recombination events in EV71

Abstract: Hand-foot-mouth disease due to enterovirus 71 (EV71) and coxsackievirus A16 (CA16) has recently caused large outbreaks in mainland China in 2008. We performed complete genome sequencing on two EV71 (SZ/HK08-5 and SZ/HK08-6) and two CA16 (SZ/HK08-3 and SZ/HK08-7) strains from patients in Shenzhen, China. Phylogenetic, similarity plot and bootscan analyses revealed recombination between EV71 genotypes B and C at the 2A-2B junction, and between EV71 genotype B and CA16 strain G-10 in the 3C region for EV71 strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 34 publications
10
89
0
Order By: Relevance
“…It is possible that the EV71 strains currently circulating in countries that suffer from severe EV71 outbreaks obtained an unidentified neurovirulence determinant(s) in the viral genome and became more neurovirulent than those that circulated previously. It is also possible that CVA16 has the potential to cause neurological disease, because it has been reported, in the case of poliovirus, that an increase in neurovirulence levels can be caused by point mutations or by genetic recombination between avirulent poliovirus vaccine strains and nonpolio enteroviruses (49,50,51,52,53,54). Because CVA7, CVA14, CVA16, and EV71 utilize the same receptor and because SCARB2-dependent viruses sometimes cocirculate during an epidemic of HFMD (1,12), these viruses might have a high potential to undergo an intertypic recombination by coinfection of a SCARB2-expressing cell in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the EV71 strains currently circulating in countries that suffer from severe EV71 outbreaks obtained an unidentified neurovirulence determinant(s) in the viral genome and became more neurovirulent than those that circulated previously. It is also possible that CVA16 has the potential to cause neurological disease, because it has been reported, in the case of poliovirus, that an increase in neurovirulence levels can be caused by point mutations or by genetic recombination between avirulent poliovirus vaccine strains and nonpolio enteroviruses (49,50,51,52,53,54). Because CVA7, CVA14, CVA16, and EV71 utilize the same receptor and because SCARB2-dependent viruses sometimes cocirculate during an epidemic of HFMD (1,12), these viruses might have a high potential to undergo an intertypic recombination by coinfection of a SCARB2-expressing cell in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Because CVA7, CVA14, CVA16, and EV71 utilize the same receptor and because SCARB2-dependent viruses sometimes cocirculate during an epidemic of HFMD (1,12), these viruses might have a high potential to undergo an intertypic recombination by coinfection of a SCARB2-expressing cell in vivo. Indeed, it has been reported that intertypic recombination occurred between EV71 and CVA16 (8,19,(54)(55)(56). Fortunately, neither severe neurological diseases caused by the intertypic recombinants between EV71 and CVA16 nor recombinant viruses of EV71 and CVA7 or CVA14 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Initial picornavirus screening was performed by amplifying a 112 bp fragment of the 59 UTR of picornaviruses using primers (59-CGGCCCCYGAATGYGGCTAA-39 and 59-ACACGGACACCCAAAGTAGT-39) targeting conserved sequences as published previously (Lau et al, 2011;Woo et al, 2010;Yip et al, 2010). Reverse transcription was performed using a SuperScript III kit (Invitrogen) and the reaction mixture (10 ml) contained RNA, firststrand buffer [50 mM Tris/HCl (pH 8.3), 75 mM KCl, 3 mM MgCl 2 ], 5 mM dithiothreitol, 50 ng random hexamers, 500 mM each dNTP and 100 U SuperScript III reverse transcriptase.…”
Section: Methodsmentioning
confidence: 99%
“…Two complete genomes of DcEV, including the full 59 UTR regions, were amplified and sequenced using strategies that we used previously for complete genome sequencing of other picornaviruses, with the RNA extracted from the faecal samples as templates (Lau et al, 2011;Woo et al, 2010;Yip et al, 2010). The RNA was converted to cDNA by a combined random-priming and oligo(dT) priming strategy.…”
Section: Methodsmentioning
confidence: 99%
“…22 Studies have shown that humans can be co-infected with CA16 and EV71, 23,24 and co-infection might increase the possibility of genetic recombination between CA16 and EV71. 25,26 This phenomenon might account for the HFMD outbreak in Mainland China in 2008. 26 Vaccines are the most efficient measure to control HFMD epidemics.…”
Section: Introductionmentioning
confidence: 99%